Hydrogen sulfide stimulates CFTR in Xenopus oocytes by activation of the cAMP/PKA signalling axis - Perniss, Alexander; Preiss, Kathrin; Nier, Marcel; Althaus, Mike; Justus Liebig University Giessen (My University, 2017)
Hydrogen sulfide (H2S) has been recognized as a signalling molecule which affects the activity of ion channels and transporters in epithelial cells. The cystic fibrosis transmembrane conductance regulator (CFTR) is an epithelial anion channel and a key regulator of electrolyte and fluid homeostasis. In this study, we investigated the regulation of CFTR by H2S. Human CFTR was heterologously expressed in Xenopus oocytes and its activity was electrophysiologically measured by microelectrode recordings. The H2S-forming sulphur salt Na2S as well as the slow-releasing H2S-liberating compound GYY4137 increased transmembrane currents of CFTR-expressing oocytes. Na2S had no effect on native, non-injected oocytes. The effect of Na2S was blocked by the CFTR inhibitor CFTR_inh172, the adenylyl cyclase inhibitor MDL 12330A, and the protein kinase A antagonist cAMPS-Rp. Na2S potentiated CFTR stimulation by forskolin, but not that by IBMX. Na2S enhanced CFTR stimulation by membrane-permeable 8Br-cAMP under inhibition of adenylyl cyclase-mediated cAMP production by MDL 12330A. These data indicate that H2S activates CFTR in Xenopus oocytes by inhibiting phosphodiesterase activity and subsequent stimulation of CFTR by cAMP-dependent protein kinase A. In epithelia, an increased CFTR activity may correspond to a pro-secretory response to H2S which may be endogenously produced by the epithelium or H2S-generating microflora.
Keywords: ddc:610